Peak kinematic and mechanical demands according to playing positions in professional male soccer: Composition analysis and characteristics of locomotor activities - Yousefian, F.; Zafar, A.; Fransson, D.; Brito, J.; Travassos, B. (Research Quarterly for Exercise and Sport, 2025)
This study examined the most demanding passages (MDP) of composite kinematic and mechanical activities in professional soccer according to positions. Global positioning system data were collected from 39 male soccer players across two seasons. Kinematic and mechanical MDP were identified by composite MDPk (maximal distance covered across moderate- and high-speed running and sprinting thresholds) and MDPm (maximal magnitude of high-intensity acceleration and deceleration efforts) criterion variables across 5 min moving average periods. Linear mixed models assessed the intensity, number of efforts, and duration of specific locomotor activities of each MDP by position. The kinematic MDP showed higher intensity, effort count, and relative duration of MDPk activities than mechanical MDP (p <= 0.001; ES: 0.7-1.7). Conversely, MDPm activities had greater magnitude, efforts, and relative duration in mechanical MDP (ES: 1.9-2.0). Similar constituent variable compositions were observed between peak periods. The MDPk comprised ~60 ± 16% moderate-speed running, ~30 ± 11% high-speed running, and ~14 ± 8% sprinting distances; MDPm included ~35 ± 23% and ~65 ± 23% high-intensity accelerations and decelerations. Positional differences revealed central defenders had lower, while full-backs and wide-midfielders had higher, MDP values. Findings from this study highlight the multidimensional characteristics of composite peak kinematic and mechanical periods in professional soccer. The differential contribution of low- and high-intensity locomotor activities during such periods, in terms of magnitude, number of efforts, and duration, should be considered by practitioners. Such insight can inform effective position-specific training prescription as well as bespoke recovery strategies based on the MDP observed during match play.